Cervical cancer screening and treatment for PLWHIV: experiences from an innovative program in Nigeria - Olabanjo Okunlola Ogunsola; Oluseye Ayodele Ajayi; Temitope Olumuyiwa Ojo; Emmanuel Osayi; Kucheli Wudiri; Babatunde Amoo; Rita Ayoka-Ikechukwu; Olufemi Ojuola Olumeyan; Chukwuemeka Ifechelobi; Prosper Okonkwo; Yewande Akinro (BMC, 2023)
Abstract Background We evaluated cervical cancer program for women living with HIV (WLHIV) to determine program screening rate, primary case finder screening accuracy and treatment and post-treatment screening rate among screen-positive patients. Methods A ten-month review of cervical cancer program data among WLHIV aged 15-49 years on HIV care across forty-one comprehensive ART sites, supported by APIN (a PEPFAR implementing partner) for cervical cancer screening and treatment in Nigeria, was conducted from October 2020 to July 2021. Initial screening was done using visual inspection with acetic acid (VIA) followed by a gynaecologist expert review through a program-designed software named AVIVA, as a confirmatory test. Associations were measured between the primary case finder screening accuracy and study covariates at p-value of 0.05. Results About 10,289 asymptomatic women aged 15-49 years living with HIV were screened for cervical cancer by primary case finders using VIA-based screening test. About 732 (7.1%) had a positive screening test suggestive of precancerous lesions or cervical cancer. Three hundred and fifteen (43.0%) of VIA positive women had treatment using thermal ablation and less than one-third (21.6%) of those treated came back for post-treatment screening test. Primary case finder screening sensitivity, specificity, positive predictive and negative predictive accuracy using gynaecologist review as confirmatory test were 60.8%, 71.5%, 41.7% and 84.5% respectively. Overall screening accuracy was 68.8%. Conclusion and recommendations This innovative approach to cervical cancer screening among WLHIV yielded modest results in preventing program error and wastages. Wider deployment of expert-based reviews of VIA though AVIVA software might be a veritable approach to improve screening accuracy in low resource settings.